(untitled) (Journal of Health, Population and Nutrition, 2011)
The aim of this observational study was to describe the profile of subjects with type 2 diabetes mellitus from Gujarat, India. The study was performed with newly-diagnosed 622 type 2 diabetic subjects who attended the Department of Diabetology, All India Institute of Diabetes and Research and Yash Diabetes Specialties Centre (Swasthya), Ahmedabad, during August 2006–January 2009. The subjects completed an interviewer- administered questionnaire. The questionnaire included variables, such as sociodemographic factors, presenting symptoms, risk profile (hypertension, obesity, dyslipidaemia, and glycaemic status), family history of diabetes, physical activity, and behavioural profile. Blood pressure, body mass index (BMI), glycosylated haemoglobin levels, and fasting lipid profile were measured. Descriptive and bivariate analyses were carried out using the SPSS software (version 11.5). In total, 622 type 2 diabetes mellitus (T2DM) cases with mean age of 47.7±10.9 years were studied. Of the 622 subjects, 384 (62%) were male. The majority (68%) of the T2DM subjects were obese, and 67% had a positive family history of diabetes. Renal dysfunctions and vision impairment were, respectively, found in 10% (n=62) and 9% (n=57) of the 622 T2DM subjects. The mean HbA1c level was 9.02±1.67%, and good glycaemic control (HbA1c level <7%) was achieved only in 7.4% of the T2DM subjects. Results of chi-square analysis showed that higher BMI (≥25 kg/m2) was significantly associated with hypertension among the T2DM subjects (p<0.01). There were significant differences (p<0.05) between male and female subjects with respect to mean age, BMI, waist- and hip-circumference, and mean low-density lipoprotein (LDL) level. The results revealed that many factors, such as obesity, family history of diabetes, dyslipidaemia, uncontrolled glycaemic status, sedentary lifestyles, and hypertension were prevalent among the T2DM subjects. The characterization of this risk profile will contribute to designing more effective and specific strategies for screening and controlling T2DM in Gujarat, India. Key words: Type 2 diabetes mellitus; Obesity; Polyuria; Glycaemic status, Dyslipidaemia; India DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7874 J HEALTH POPUL NUTR 2011 Jun;29(3):265-272